Effect of the Brazilian thermal modification process on the chemical composition of Eucalyptus grandis juvenile wood - Part 1: Cell wall polymers and extractives contents - Batista, Djeison Cesar; Bolzón de Muñiz, Graciela Ines; da Silva Oliveira, José Tarcísio; Benigno Paes, Juarez; Nisgoski, Silvana (Maderas. Ciencia y Tecnología, 2016)
This article reports the first study of the influence of the Brazilian process of thermal modification called VAP HolzSysteme® on the chemical composition of Eucalyptus wood. Flatsawn boards of Eucalyptus grandis juvenile wood were tested for four treatment levels: untreated and thermally modified at final cycle temperatures of 140, 160 and 180 °C. Chemical analyses were carried out according to the standards of the Technical Association of the Pulp and Paper Industry and encompassed total extractives, insoluble lignin, holocellulose (cellulose + hemicelluloses) and solvent soluble extractives in water (cold and hot) and ethanol:toluene (1:2 v.v.) mixture. The chemical composition of thermally modified Eucalyptus grandis juvenile wood was significantly changed by the VAP HolzSysteme® process compared to untreated wood. Only the wood thermally modified at final cycle temperature of 180 °C was significantly different for all the chemical analyses performed compared to untreated wood.